2009
DOI: 10.1590/s0370-44672009000400004
|View full text |Cite
|
Sign up to set email alerts
|

A intrusão diamantífera Abel Régis (Carmo do Paranaíba, MG): kimberlito ou lamproíto?

Abstract: Centenas de intrusões de natureza kimberlítica ou relacionadas são conhecidas na Província Diamantífera do Alto Paranaíba, em Minas Gerais e Goiás. O pipe Abel Régis, localizado em Carmo do Paranaíba e descoberto pela De Beers na década de 1970, é um desses corpos, que tem sido, em geral, considerado como um kimberlito. Na área da intrusão, ocorrem metassedimentos neoproterozóicos do Grupo Bambuí, os quais são atravessados pelo pipe cretácico (?) de forma superficial aproximadamente circular, com cerca de 1.40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Crystallization temperatures of Alfeu-I lamproite were determined using the olivine-spinel Mg-Fe 2+ exchange geothermometer of O' Neill and Wall (1987) and Ballhaus et al (1991), who applied their geothermometer to peridotite xenoliths. We used chromites and olivines microcrysts analyses of Alfeu-I lamproite (Chaves et al 2014, Provenzano 2016; and this study -Table 3 and Suppl. data) from mineral separates, as the Alfeu-I pipe is unfortunately very altered and it was not possible to collect preserved samples.…”
Section: Geothermobarometry and Oxygen Barometry Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystallization temperatures of Alfeu-I lamproite were determined using the olivine-spinel Mg-Fe 2+ exchange geothermometer of O' Neill and Wall (1987) and Ballhaus et al (1991), who applied their geothermometer to peridotite xenoliths. We used chromites and olivines microcrysts analyses of Alfeu-I lamproite (Chaves et al 2014, Provenzano 2016; and this study -Table 3 and Suppl. data) from mineral separates, as the Alfeu-I pipe is unfortunately very altered and it was not possible to collect preserved samples.…”
Section: Geothermobarometry and Oxygen Barometry Resultsmentioning
confidence: 99%
“…Olivine compositions are from this study. Chromite compositions from Chaves et al (2014). Olivines (Ol), chromites (Chr), ΔFMQ (fO 2 relative to FMQ buffer), and standard deviations (stdev) as last significant digits in brackets.…”
Section: Sr-nd Isotope Datamentioning
confidence: 99%
“…The occurrence of G5 and G9 garnets and low-MgO ilmenite in the lamproitic pipe Abel Régis (Chaves et al 2009), can be related to the mineral assembly found in the diamond deposit of Romaria, suggesting a lamproitic source, although primary rock was not found to characterize the representative faciologies of this type of diamond-bearing rock.…”
Section: General Implicationsmentioning
confidence: 91%
“…The volcanoclastic sequence of the Água Suja Mine (GAR-Mineração and surroundings) has been correlated to the Marília Dias 2017, Seer andMoraes 2017) or the Uberaba Formation (Gravina et al 2002, Gravina 2003. Chaves et al (2009) worked with the Abel Régis (Carmo do Paranaíba, Minas Gerais state, Brazil) lamproitic intrusion where there is a high concentration of garnets in the G5 and G9 fields of Grutter et al (2004) and MgO-poor ilmenites. Kaminsky and Belousova (2009) identified manganese ilmenite in kimberlitic pipes from to the Juina kimberlitic field (Mato Grosso state, Brazil).G5 garnets are interpreted by Grutter et al (2004) as indicative of a destroyed lithosphere and are also correlated to lamproitic rocks when associated with manganoan ilmenites and dravitic tourmalines (Fipke 1991, Presser 2019.…”
Section: General Implicationsmentioning
confidence: 99%
“…The grey areas in (a) and (b) represent the composition of the clinopyroxene of mantle xenoliths and concentrates of the kimberlites from Rondônia (196 analyses) and APIP (1322 analyses), respectively, from previous works. Data compilation from: Costa (1996), Carvalho (1997), Zolinger (2005), Chaves (2008a), Costa (2008), Silva (2008), Melluso et al (2008), Almeida (2009), Chaves et al (2009), Thomaz (2009), Hunt et al (2009), Nannini (2011), Andrade (2012), Guarino et al (2013), Nannini (2016) and Gervasoni et al (2022).…”
Section: Major Element Compositionmentioning
confidence: 99%